Evaluation of Solidification History Dependent Crystal Defects Using X-ray Diffraction - Azersky, Colby. (Tufts University. Tisch Library., 2024)
Thesis (Ph.D.)--Tufts University, 2024.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Douglas Matson.; Committee: Jannatun Nawer, Ayse Asatekin, and Hani Henein.; Keyword: Mechanical engineering.